Impacts of adding functional oils or sodium monensin in high-concentrate diets on performance, feeding behaviour and rumen morphometrics of finishing Nellore cattle - Melo, A. C. B. [UNESP]; Pereira, M. C. S. [UNESP]; Rigueiro, A. L. N. [UNESP]; Estevam, D. D. [UNESP]; Toledo, A. F. [UNESP]; Assumpcao, A. H. P. M. [UNESP]; Dellaqua, J. V. T. [UNESP]; Lelis, A. L. J. [UNESP]; Millen, D. D. [UNESP] (Cambridge Univ Press, 2020)
This study, conducted at the Sao Paulo State University feedlot, Dracena campus, Brazil, was designed as a completely randomized block with 2 x 2 factorial arrangement of treatments to evaluate the effects of adding functional oils (FO) or sodium monensin (MON) on feedlot performance, carcass traits, feeding behaviour and rumen morphometrics of Nellore cattle. Ninety-six 20-mo-old Nellore bulls (365.52 +/- 39.19 kg) were randomly allocated to 24 pens (n= 4/pen), which were assigned to the treatments: (1) Control (no feed additives); (2) FO (500 ppm); (3) MON (27 ppm); and (4) MON + FO (27 + 500 ppm, respectively). Each treatment was replicated 6 times, and cattle were fed for 105 days. From 0 to 28 days on feed, cattle fed FO had lower dry matter intake (DMI) variation, sorted for medium particles and presented smaller papillae width. The feeding of FO did not negatively impact feedlot performance overall. When MON was added to the diet, cattle had lower DMI overall and 12th rib fat daily gain, and improved gain to feed ratio. The addition of MON to diets improved feedlot performance but reduced the rate of carcass fat deposition. The few effects observed when FO was added to diets were not sufficient to impact feedlot performance.
Keywords: Additives; behaviour; ionophore; papillae; performance